The Impact of Language of Instruction on Teachers' Learning Practices in Primary Schools and Secondary Schools in Dili, Timor-Leste, and Its Implications in Preparing Human Resources - Soares, Januario; Prabawa, Titi Susilowati; Listyani, Listyani (International Journal of Language Teaching and Education, 2025)
This study analyzes the impact of using Portuguese and Tetun as languages of instruction in primary and secondary schools in Dili, Timor Leste, and its implications for human resource development. While Tetun facilitates students' understanding in local contexts, its limited global relevance presents a challenge. Conversely, Portuguese, though internationally recognized, is not fluently spoken by most teachers and students, reducing the effectiveness of the teaching and learning process. This qualitative research involved 68 informants, including education officials, principals, teachers, and students across Dili. Data were collected through interviews, observations, and documentation. The findings reveal that language barriers, particularly in Portuguese, negatively affect classroom interaction, leading to poor student comprehension and low academic achievement. This situation may hinder the development of quality human resources capable of competing globally. The study recommends that the Timor Leste government and Ministry of Education intensify Portuguese training for both teachers and students, allocate funds for Tetun development, offer incentives to high-performing teachers, and encourage the consistent use of the instructional Language at home and in school, drawing from practices in Cuba and Venezuela. Strengthening language proficiency among educators and learners is essential to improving education quality and supporting Timor-Leste's broader socio-economic advancement.